Village Government Strategy in Strengthening Religious Tolerance in the Community in Hoelea I snd Hoelea II Villages - Abdullah, Ramadhan; Haris, Abdul; Yazid, Syamsurizal (EDUMALSYS Journal of Research in Education Management, 2025)
This study aims to understand the village government's strategy in strengthening tolerance values ​​in the community in Hoelea I and Hoelea II Villages. This study uses a qualitative approach with a case study type. The research subjects consisted of village heads, community leaders, religious leaders, and villagers randomly. Data collection techniques were carried out through observation, interviews, and documentation. Data validity testing was carried out by triangulating sources and techniques, while data analysis was carried out using Miles and Huberman's interactive analysis techniques. The results of the study indicate that the village government's strategy in strengthening religious tolerance in the Hoelea I and Hoelea II village communities is carried out by fostering religious attitudes, instilling values ​​of mutual respect and respect, harmonious communication, cooperation and religious freedom and implementing the principles of tolerance education. This study underlines the importance of collective commitment from village government authorities, religious leaders and community members to foster mutual respect and maintain peaceful coexistence.